Coordinated Spatio-Temporal Operation of Wind–Solar–Storage-Powered Data Centers Considering Building Thermal Inertia - Xuexue Qin; Xiangyu Zhai; Jiahui Zhang; Xiaoyang Liu; Xiang Bai; Chuanjian Wu; Longwen Chang; Zening Li (Buildings)
In the context of the booming digital economy, the energy consumption of data centers (DC) is experiencing exponential growth, and achieving green transformation has become a crucial issue. This paper presents a coordinated spatio-temporal operation of wind–solar–storage-powered DCs considering building thermal inertia. Firstly, based on users’ differentiated needs, the spatio-temporal flexibility of data loads is deeply explored to lower DC’s operation costs through load shifting. Secondly, a DC mathematical model considering building thermal inertia is established, revealing the quantitative relationship among air-conditioning power, data load rate, and building parameters. Finally, a coordinated spatio-temporal operation of wind–solar–storage-powered DCs considering building thermal inertia is proposed to promote renewable energy consumption and realize the green transformation of DC. The case study results show that the proposed strategy reduces the DC operation cost by 37.92% and significantly increases the renewable energy-consumption ratio.